Kinetics of the Valorization of Food Waste for Medium Chain Carboxylates Production; Effect of Ensiling and Inoculum source. - Undiandeye, J. A.; Obiora-Okafo, I.; Idama, E. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
Higher yields of medium chain carboxylates (MCC) can be obtained from the anaerobic fermentation of complex feedstocks like food waste if pretreatment preceeds fermentation. However, many conventional pretreatment processes produce inhibitors that could affect downstream processing in addition to increasing the cost of the overall process. In this study, ensiling was used as a cost effective and sustainable pretreatment method to instigate the formation of electron donors like lactic acid and ethanol in food waste for MCC production. Food waste was ensiled for 120 days and thereafter subjected to batch anaerobic fermentation using two different inocula including leachate and rumen fluid. Results show that ensiling degraded the cellulose and hemicellulose component of food waste and converted the water soluble carbohydrate content to lactic acid, acetic acid and ethanol. Ensiled substrates had a total MCC yield of 990.44 g/kgVS and 878.68 g/kg VS when leachate and rumen fluid was used as inoculum respectively, while the unensiled food waste had a total MCC yield of 522.80 g/kgVS and 430.88 g/kgVS when leachate and rumen fluid was respectively used as inoculum. In order to predict the MCC production, two kinetic models were used including the first-order model and the modified Gompertz model. Statistical indicators including the coefficient of determination, R2, the root-mean-square-error and the Akaike Information Criterion show that the first-order model predicted the experimental MCC better than the modified Gompertz model.